ICBTBYOFAUNAL DIVERSITY OF GREAT NICOBAR ISLAND, BAY OF BENGAL - Rajaram, R.; Srinivasan, M.; Khan, S. Ajmal; Kannan, L. (Journal of Indian Fisheries Association, 2015)
Ichthyofauna was studied in the inshore waters around the Great NicobarIsland to assess the extent of biodiversity of fishery resources in the GreatNicobar watersÂ· by using various gears and crafts. During the present study,258 species of fin fishes belonging to 141 genera, 84 families and 19 orderswere recorded. Among these, Perciformes topped the list with 4 7 families, 84genera and 169 species followed by Clupeiformes, Angulliformes,Tetrodoniformes, Cyprinodontiformes, Scorpaeniformes, Rajiformes,Elopiformes, Pleuronectiformes, Syluriformes, Laminiformes, Bercyformes,Aelopiformes, Syngathiformes and Gonorhychiformes which includes themedicinally important and ornamentally valuable species.Keywords: Ichthyofauna, diversity, Nicobar Island